Copper‐Catalyzed Cyanoalkylative Aziridination of N‐Sulfonyl Allylamines. Issue 11 (8th April 2020) - Ha, Tu M.; Guo, Weisi; Wang, Qian; Zhu, Jieping
Abstract: Reaction of N ‐arylsulfonyl allylamines with alkyl nitriles in the presence of di‐ tert ‐butyl peroxide (DTBP) and a catalytic amount of copper salt afforded homologated aziridines in 43–86% yield. A sequence involving addition of the in situ generated cyanomethyl radical to the double bond followed by a copper‐mediated intramolecular C−N bond formation accounted for the reaction outcome. 2, 3‐Disubstituted allylamines were converted to trisubstituted aziridines in a stereoselective manner. Starting from enantioenriched allylamines, chiral aziridines were obtained diastereoselectively. Abstract :